Acute-onset chronic inflammatory demyelinating polyneuropathy in hantavirus and hepatitis B virus coinfection: A case report. Issue 49 (December 2016) - Lim, Jong Youb; Lim, Young-Ho; Choi, Eun-Hi
Abstract: Introduction: Chronic inflammatory demyelinating polyneuropathy (CIDP) is an acquired autoimmune disorder with progressive weakness. Acute-onset CIDP resembles Guillain-Barre syndrome (GBS), a rapidly progressive disorder, and follows a chronic course. To our knowledge, no case of acute-onset CIDP in hantavirus and hepatitis B virus (HBV) coinfection has been reported previously. Clinical findings: We report a case of acute-onset CIDP that was initially diagnosed as GBS. Diagnoses: A 44-year-old male logger complained of acute quadriplegia and dyspnea. Mechanical ventilation was initiated. He was an HBV carrier with mild elevation of hepatic enzyme, and positive for hantavirus antibody. He was diagnosed with GBS and immunoglobulin therapy was administered. Interventions: After 8 months, quadriplegia and hypesthesia recurred. Immunoglobulin therapy at this time had no effect, but steroid therapy had some effect. Outcomes: A diagnosis of CIDP was made. After 2 months, severe extremity pain and dyspnea developed again, and steroid pulse therapy was initiated. Conclusion: Besides GBS, acute-onset CIDP can occur with hantavirus and HBV coinfection. Patients with this coinfection in whom GBS has been initially diagnosed should be followed up for a long time, because of the possibility of relapse or deterioration, and acute-onset CIDP should always be considered.